NEW APPROACHES IN EDUCATION OF ARTISTIC GYMNASTICS - DRACKOVA, Dana; MONKA, Peter (Trends in education, 2009)
The article deals with the requirement of a handbook creation for the theory and methodology of artistic gymnastics. This handbook should be done in electronic version and it should have all the attributes that are needed for the increasing of education effectivity and for faster drill achievement on the lessons of artistic gymnastics. The utilization of computer aid plays substantial role at the goals achievement. The article is direct supported from grant KEGA no.3/5173/07 of Cultural and Educational Grant Agency of Ministry of Education of Slovak republic
Keywords: visualization; computer aid; artistic gymnastic; elements.